New Alicornops (Rhinocerotidae) remains from Lower and Middle Siwaliks, Pakistan - Khan, Abdul Majid (2012)
Unpublished rhinocerotid remains from the Lower and Middle Siwaliks of Pakistan are described in this paper and recognized as two species of Alicornops. Alicornops complanatum (Heissig) is identified in the Dhok Pathan Formation of the Middle Siwaliks and Alicornops laogouense Deng in the Kamlial Formation of the Lower Siwaliks. The Dhok Pathan Formation levels with A. complanatum are roughly correlated with the late Miocene-Pliocene European mammal zones MN10-15. In turn, levels with A. laogouenseof the Kamlial Formation would correlate with the middle–late Aragonian (middle Miocene) European MN5. The recognition of the Chinese species A. laogouense in the Potwar Plateau represents the first discovery of this taxon in Pakistan and increases the geographical and stratigraphic distributions of this species, and adds to the rhinocerotid association from the Siwaliks. In turn, the presence of A. complanatum in the Siwaliks of Potwar Plateau also enlarges its geographic distribution in Pakistan, as it was previously known from the Bugti Hills of Balouchistan. The absence of Alicornops from the Siwaliks in the Chinji and Nagri formations (between late MN5 and MN9 zones) might be due to an inadequate fossil record, as other rhinocerotid species are known from Kamlial to Dhok Pathan formations. However, the two recorded species of Alicornops could also reveal two independent migration waves as supported by the appearance of other taxa in different formations. A summary of fossil Cenozoic rhinocerotids from different areas of Pakistan is also presented.